2018
DOI: 10.1371/journal.pone.0206414
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the competence of midwives to provide care during labor, childbirth and the immediate postpartum period – A cross sectional study in Tigray region, Ethiopia

Abstract: BackgroundThe availability of a skilled birth attendant is widely recognized as a critical factor in reducing maternal and newborn mortality. Competence of maternal healthcare providers directly affects quality of care and health outcomes. This study assessed competence of midwives and associated factors in provision of care during labor, and the immediate postpartum period at public health facilities in Tigray, Ethiopia.MethodsA cross-sectional study design was employed to collect data through direct observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The Ethiopian government made various efforts towards making safe-motherhood a priority. Launching a number of midwifery training programs, 29 health extension programs (HEP), 8 and scaling-up MWHs, 9 which were initially concentrated at the hospital level but have more recently been implemented at health centers, are some of the initiatives illustrating these efforts. Proper implementation of MWHs at the health centre level improved access to the basic emergency obstetric and newborn care (BEmONC), 30,31 which constitutes the seven signal functions: administering parenteral antibiotics, oxytocic drugs, and anticonvulsants; manual removal of the placenta and retained products; and perform assisted vaginal birth and, basic neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The Ethiopian government made various efforts towards making safe-motherhood a priority. Launching a number of midwifery training programs, 29 health extension programs (HEP), 8 and scaling-up MWHs, 9 which were initially concentrated at the hospital level but have more recently been implemented at health centers, are some of the initiatives illustrating these efforts. Proper implementation of MWHs at the health centre level improved access to the basic emergency obstetric and newborn care (BEmONC), 30,31 which constitutes the seven signal functions: administering parenteral antibiotics, oxytocic drugs, and anticonvulsants; manual removal of the placenta and retained products; and perform assisted vaginal birth and, basic neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The Lancet Commission on High Quality Health Systems revealed that the quality of obstetric and newborn health services remains poor and variable across low-and middleincome countries (LMICs) [1][2][3][4]. Inadequate healthcare provider competence has been identified as a contributing factor to the widespread poor quality care found in many LMICs [5][6][7][8]. Increasing care competence is one of the key strategy to improve health outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…As data on the competence of NPAs is so scarce globally, comparison with similar studies was not possible. However, competence studies involving nurses [ 38 , 39 ], midwives [ 40 , 41 ], and other allied healthcare providers [ 42 ] across the LMICs have shown that acquiring sufficient competency levels is a global educational challenge.…”
Section: Discussionmentioning
confidence: 99%